2020
DOI: 10.1186/s13054-019-2723-z
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory flow limitation developed in ICU patients: relationship of fluid overload, respiratory mechanics, and outcome

Abstract: Dear editor, We read with great interest in the report by Volta and colleagues [1] about the presence and determinant of expiratory flow limitation (EFL) developed in patients admitted to an intensive care unit (ICU). They found that the presence of EFL is common among ICU patients requiring mechanical ventilation for acute respiratory failure of different etiologies. And interestingly, the major determinant for developing EFL in patients during the first 3 days of their ICU stay is a positive fluid balance. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The MR-ProADM levels did not correlate with AKI incidents, but discriminated patients with high odds of death. The latest study of Liu et al [ 65 ] performed in a group of critically ill sepsis patients suggested that ADM may become a biomarker for rapid assessment of the presence and severity of AKI at an early stage.…”
Section: Significance Of Adm In Kidney Diseasesmentioning
confidence: 99%
“…The MR-ProADM levels did not correlate with AKI incidents, but discriminated patients with high odds of death. The latest study of Liu et al [ 65 ] performed in a group of critically ill sepsis patients suggested that ADM may become a biomarker for rapid assessment of the presence and severity of AKI at an early stage.…”
Section: Significance Of Adm In Kidney Diseasesmentioning
confidence: 99%
“…Several articles have been published analyzing adaptations required in emergency, radiology and intensive care departments ( Ashari et al, 2020 , Wee et al, 2020 , Vargas et al, 2020 ). However, we were not able to find virtually nothing about the great challenge that the pandemic has posed to Clinical Microbiology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…There are restrictions on ensuring patient comfort in ICU, and specific methods may vary depending on the studies. However, the common emphasis in previous studies is that it is important to maintain the physical and mental comfort of the patient during the time of death and involve the patient and his or her family as soon as possible in this decision-making for treatment at the end of life [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%